ANALYSIS 4E (ENERGY - EXERGETIC - ECONOMIC - ENVIRONMENTAL) OF A STEAM HEATING POWER PLANT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The energy, exergy, economic and environmental analysis of steam power plants is necessary to identify the most efficient and viable configuration. In this regard, we have developed a model to simulate the performance of a steam power plant (with a capacity of 210 MW) intended for the production of electrical energy. In this respect, a 4E study (energy – exergy – economic – environmental) was carried out. According to the results obtained, the configuration studied presents energy and exergy performances of 41.9% and 39.5% respectively. In addition, reducing the steam pressure at the condenser plays a major role in improving plant performance. On the other hand, increasing the pressure and temperature of the steam at the inlet of the turbine increases the thermodynamic and environmental performance of the installation.
Keywords: Steam plant; Configuration; 4E study; Modelization; Performance